2010
DOI: 10.1093/ntr/ntq158
|View full text |Cite
|
Sign up to set email alerts
|

Brief Smoking Cessation Intervention in Relation to Breast Cancer Surgery: A Randomized Controlled Trial

Abstract: Brief smoking intervention administered shortly before breast cancer surgery modestly increased self-reported perioperative smoking cessation without having any clinical impact on postoperative complications. The study adds to the body of evidence indicating that brief intervention has no clinical importance for surgical patients in regard to postoperative morbidity. Future studies should be designed to determine the optimal time of smoking cessation before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(121 citation statements)
references
References 22 publications
0
120
0
1
Order By: Relevance
“…The two primary settings in which smoking cessation interventions were offered were during the perioperative period or within the clinic. In the perioperative setting, 15,66,68,72,73 the pooled OR was 2.31 (95% CI, 1.32-4.07; I 2 = 0%) ( Figure 6). Finally, a subgroup analysis looking at studies with only self-reported tobacco cessation 15,66,68,72,73 (Figure 8) showed a more favorable result for smoking cessation in patients who had biochemical verification of cessation.…”
Section: Tobacco Cessation Rates and Follow-upmentioning
confidence: 99%
See 3 more Smart Citations
“…The two primary settings in which smoking cessation interventions were offered were during the perioperative period or within the clinic. In the perioperative setting, 15,66,68,72,73 the pooled OR was 2.31 (95% CI, 1.32-4.07; I 2 = 0%) ( Figure 6). Finally, a subgroup analysis looking at studies with only self-reported tobacco cessation 15,66,68,72,73 (Figure 8) showed a more favorable result for smoking cessation in patients who had biochemical verification of cessation.…”
Section: Tobacco Cessation Rates and Follow-upmentioning
confidence: 99%
“…Ten RCTs 5,15,16,[66][67][68][69][70][71][72] and 3 PC studies 21,73,74 met the inclusion criteria (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar work has already been pursued among anesthesiologists to promote long-term risk-factor reduction in the case of smoking cessation. 54-58 Specifically, regarding elevated blood pressure, several multidisciplinary cooperative efforts among nurses, pharmacists and other physician specialists, including surgeons, have demonstrated the potential feasibility of this idea for addressing the urgent and persistent public health need of improving the longitudinal control of elevated outpatient blood pressure. 59-62 …”
Section: Discussionmentioning
confidence: 99%